My Amputations - Major, Clarence (Book collections on Project MUSE., 2008)
The author of the acclaimed novel, Reflex and Bone Structure, returns here in My Amputations, to the question of identity, the double, adventure, detection and mystery, but with more hypnotic power and range. In My Amputations he has his protagonist, Mason Ellis, (who may just be ""a desperate ex-con"" or a wronged American novelist out to right the wrong done to him) jump through flaming loops like a trained dog, so to speak. In other words, there seems to be no end to the troubles Mason Ellis faces. His story takes him from the South Side of Chicago, to New York, with a stint in Attica priso.